Experimental Study Using Recycled Waste Tyre as Sustainable Clay Soil Stabilisation - Md Zain, Nor Hazwani; Mohd Salim, Nurul Ainain; Saiful Bahri, Intan Shafika; Md Yusof, Zeety (International Journal of Integrated Engineering, 2022)
Clay presents construction challenges to geotechnical engineers as it shows high compressibility, low shear strength and high level of volumetric changes behaviour. Therefore, the properties of clay need to be improved before it can be used in any type of construction. Clay soil stabilisation using either mechanical or chemical methods are normally adopted to improve its properties. However, some of these methods are reported to be ineffective, expensive and harmful to the environment. In Malaysia, around 8.2 million tyres are dumped in landfill annually. The dumping of tyres will lead to long-term environmental impact. Hence, it is proposed to reuse waste tyres for clay soil stabilisation. This research investigates the effects of recycled waste tyres on the compaction and strength properties of clay soil. Clay soils were firstly mixed with 0, 5, 10, 15 and 20% of waste tyres and each mixed sample was tested for compaction and unconfined compressive strength tests. The results show that the optimum moisture content (OMC) increases and maximum dry density (MDD) decreases with increasing waste tyre content. Meanwhile, unconfined compressive strength (UCS) reaches a maximum value at 10% waste tyre content and then decreases with further increments of waste tyre. It can be concluded that waste tyres have the potential to be used as an additive for sustainable clay soil stabilisation.